Reproductive Biology of Common Carp(Cyprinus carpio L. ) from AL-Gharraf Canal , at Wasit Province –Iraq.I. Sex-Ratio and Maturity - Hamady, A. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
From September 2002 to August 2003 monthly samples of fish were collected from two stations at the area of study. The results of the present study showed that the sex-ratio (male: female) was 1:0.95. Sexual maturity was reached by all fishes above 28 cm in total length , the smallest mature male was 21.3 cm in total length and body weight 164 gm. While the smallest mature female was 21.5 cm in T.L. and body weight 155 gm. The mature male and female were in the second year of their ages. The breeding season extended from the end of February until the end of June and another season started from September to November.